Mesangioproliferative Glomerulonephritis: A 30-Year Prognosis Study - Axelsen, Mette (S. Karger AG, 2014)
BACKGROUND: Diffuse mesangioproliferative glomerulonephritis (MesP) is the most commonly diagnosed type of glomerulonephritis (GN) in Denmark, with an incidence of 10.8 million per year. In the present study, the 30-year renal survival was estimated. METHODS: A retrospective cohort investigation of 140 patients with biopsy-proven MesP was performed between the period 1967-2006. Factors influencing renal survival were investigated using Cox regression analysis. RESULTS: Renal survival at 5, 10, 20 and 30 years was 87, 78, 59 and 50%, respectively. Female survival after 30 years was significantly better than male survival (70 vs. 40%, p = 0.049). Multivariate analysis, adjusted for age, estimated glomerular filtration rate (GFR) and nephrotic syndrome (NS) was performed for each sex individually. An increase in GFR was associated with a hazard risk (HR) of 0.98 (p = 0.02) in women and 0.99 (p = 0.006) in men. Older age was associated with a HR of 1.04 (p = 0.02) in women and 1.03 (p = 0.004) in men. NS had a poorer prognosis in men (HR 2.53, p = 0.01), but not in women (HR 0.54, p = 0.38). CONCLUSION: Increasing age and decreasing GFR were adversely associated with renal death. Renal prognosis was better for women after 30 years, and NS resulted in a poorer prognosis in men. This suggests that disease course and prognosis are different between men and women.